Screening for cystic echinococcosis in an endemic region of Peru using portable ultrasonography and the enzyme-linked immunoelectrotransfer blot (EITB) assay - Moro P.L. (2005)
Financial support for this study was received from Consejo Nacional de Ciencia y Tecnología (CONCYTEC), Lima, Peru. The methods used in the present study comply with current Peruvian law governing the participation of human subjects in biomedical research.